Cyber law in developing countries: An Indian Perspective (Journal of The Colloquium for Information Systems Security Education, 2016)
This paper provides a comprehensive overview of the relevant topics linked to the various aspects of cyber crime and focuses on the circumstances in India as developing countries. The paper contains four main topics. After an introduction (1st topic), it provides an overview of the phenomena of cyber crime and its causes (2nd topic). It followed descriptions of kinds of cyber crimes are committed in India and explanations as to why they have might be committed. An overview of the legal instruments over cyber crime is also provided in it (3rd topic). It continues with an analysis of different case laws with regard to cyber crime, its procedural law, digital evidence (4th topic).
Keywords: Cyber Stalking; Cyber hacking; Cyber Fraud; Cyber Pornography; Cyber Defamation; Software piracy; Cyber Terrorism; Cyber Phishing; Email Spoofing